10.1177/1056789514562152 (CrossRef Listing of Deleted DOIs, 2015)
The European Health Data Space (EHDS) reconfigures continuity of care by framing healthcare delivery around 'specific episodes of care' and supporting cross-border interoperability of electronic health data. Rather than relying primarily on sustained interpersonal relationships between patients and healthcare professionals, the EHDS seeks to secure continuity through institutionalised informational infrastructures that enable timely access to standardised electronic records across settings and jurisdictions.This paper examines the ethical implications of this shift for nursing practice. Based on the conceptual distinctions between relational continuity, informational continuity, and managerial continuity, we argue that while the EHDS strengthens informational continuity, it does not secure the ethical goods traditionally sustained through relational continuity, including trust, meaningful informed consent, and clearly allocated accountability. Nurses occupy a pivotal position at the intersection of documentation, interpretation, and patient communication, and thus bear newly intensified ethical and legal burdens within episodic, data-driven care environments.We analyse three emerging areas of concern: trust-building under conditions of mediated data access, the growing demand for supporting patient autonomy in cross-border data governance, and the diffusion of accountability across fragmented care episodes. The paper concludes by proposing institutional safeguards, including structured training, standard operating procedures, participatory system design, and clearer responsibility allocation, to ensure that informational continuity can coexist with ethically defensible nursing practice. In doing so, we offer an interpretative account of how data infrastructures reshape the moral landscape of care without reducing nursing ethics to data governance alone.